Perioperative role of oral gabapentin as an analgesic in paediatric patients: A randomised controlled trial - Chandni Sinha; Amarjeet Kumar; Ajeet Kumar; Poonam Kumari; Abhyuday Kumar; Bindey Kumar (Wolters Kluwer Medknow Publications, 2023)
Background and Aims: Surgical procedure commonly performed in the advanced pediatric age group includes urogenital surgery, adenotonsillectomy, etc., Aim: The aim of this study is to determine the effect of single-dose gabapentin 15 mg/kg on acute pain in the immediate postoperative period in patients aged 8-14 years undergoing surgeries under general anesthesia. Material and Methods: After the approval from the institutional ethical committee, 60 American Society of Anesthesiologists (ASA) I and II patients aged 8-14 years undergoing urogenital surgeries (orchidopexy/urethroplasty) under general anesthesia were included in this study. The patients were assigned into one of the two treatment groups. Patients in group I received oral gabapentin 15 mg/kg dissolved in 5 mL of honey 2 h before surgery, while patients in group II received 5 mL honey orally 2 h before surgery. Results: A total of 60 patients participated. Patients in group I had lower consumption of fentanyl perioperatively (intraoperatively: 1.36 ± 0.70 mcg/kg; postoperatively: 2.36 ± 0.795 mcg/kg) than group II (intraoperatively: 1.8 ± 0.6 mcg/kg; postoperatively: 2.9 ± 0.47 mcg/kg). The differences in the two groups were significant. The time to first rescue analgesia was greater in group I (3.03 ± 0.60 h) than in group II (2.26 ± 0.57 h). There was an increase in sedation score in the treatment group. Conclusion: Our clinical study demonstrates that a 15 mg/kg single preemptive oral dose of gabapentin might reduce the requirement of analgesics perioperatively in pediatric urogenital surgery but might also be associated with undesirable effects such as increased sedation.